ANALYZING THE INTROJECTED REGULATION TOWARDS STUDENTS’ LEARNING ACHIEVEMENT IN ENGLISH LANGUAGE EDUCATION STUDY PROGRAM - Aditya Sahrul Akbar; Elysa Hartati (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2020)
Learning achievement is the result of learning achieved by a student. However, students often experience difficulties in achieving good academic achievement. This study aims to analyze the relationship between introjected regulation and academic achievement. Thirty two (32) student samples were used in this study to respond to the research instruments compiled based on the theory of Ryan and Deci (2002). The results of this study indicate that r = 0.408 (p <0.05), which means there is a significant relationship between introjected regulation and learning achievement. The results of this study could be a reference for lecturers to form introjected regulation by generating positive feelings, such as happy and enjoy, in order to support the existence of student motivation.